An International Comparison of Household Expenditure Patterns, Commemorating the Centenary of Engel's Law - Houthakker, H. S. (Econometrica, 1957)
FEW DATES in the history of econometrics are more significant than 1857. In that year Ernst Engel (1821-1896) published a study on the conditions of production and consumption in the Kingdom of Saxony [6], in which he formulated an empirical law concerning the relation between income and expenditure on food. Engel's law, as it has since become known, states that the proportion of income spent on food declines as income rises. Its original statement was mainly based on an examination of about two hundred budgets of Belgian laborers collected by Ducp6tiaux. Since that date the law has been found to hold in many other budget surveys; similar laws have also been formulated for other items of expenditture. With the formulation of Engel's law an important branch of econometrics took its start, though it was not until our days that consumption research was placed on a sound theoretical and statistical basis. It is proper that in this centennial year econometricians should pay tribute tzo one of their most illustrious precursors. His successful attempt to derive meaningful regularities from seemingly arbitrary observations will always be an inspiring example to the profession, the more so because in his day economic theory and statistical techniques were of little assistance in such an attempt. There can, I think, be no more fitting tribute to this enlightened empiricist than a further inquiry into the subject to which he devoted much of his life's work. There is no need to go into details of Engel's analysis and of the developments that preceded it, for these matters have recently been discussed in the scholarly article by Stigler [13]. It should be enough to note that Engel was mainly influenced by two of his older contemporaries. One was the French engineer Fred6ric Le Play, who had collected budgets from households all over Europe, mostly, it seems, from humanitarian interest. Engel had been Le Play's student at the Ecole des Mines in Paris. The other main influence was the Belgian statistician Qu6telet, who was a firm propoinent of the idea that human characteristics, at least in the average, were governed by laws as definiite as those which govern